Natural killer T cell and pathophysiology of asthma - Gwang Cheon Jang (Korean Journal of Pediatrics, 2010)
Natural killer T (NKT) cell is a special type of T lymphocytes that has both receptor of natural killer (NK) cell (NK1.1, CD161c) and T cell (TCR) and express a conserved or invariant T cell receptor called V?#7284;J?#7288; in mice or Va24 in humans. Invariant NKT (iNKT) cell recognizes lipid antigen presented by CD1d molecules. Marine-sponge-derived glycolipid, ?#7008;galactosylceremide (?#6983;alCer), binds CD1d at the cell surface of antigen-presenting cells and is presented to iNKT cells. Within hours, iNKT cells become activated and start to secrete Interleukin-4 and interferon-?#15264;NKT cell prevents autoimmune diseases, such as type 1 diabetes, experimental allergic encephalomyelitis, systemic lupus erythematous, inflammatory colitis, and Graves' thyroiditis, by activation with ?#6983;alCer. In addition, NKT cell is associated with infectious diseases by mycobacteria, leshmania, and virus. Moreover NKT cell is associated with asthma, especially CD4+ iNKT cells. In this review, I will discuss the characteristics of NKT cell and the association with inflammatory diseases, especially asthma.